Analisis Faktor-Faktor yang Memengaruhi Penggunaan KMSPico Untuk Aktivasi Produk Microsoft Pada Mahasiswa Universitas XYZ - Muhammad Faizal Ismail; Ari Kusyanti; Admaja Dwi Herlambang (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
The use of computer in modern days is almost a necessity for everyone. Based on data from BSA Global Survey in 2015, use of pirated software in Indonesia reaches 84 percent. KMSPico is an application that can be used as an activator for Microsoft products like Microsoft Windows and Microsoft Office for free. However university of XYZ has a cooperation program with Microsoft by name of DreamSpark. DreamSpark is a program from Microsoft that supports technical education by providing access to various Microsoft products for free. In this study, the researchers conducted a non parametric analyzed with Kendall Tau to determine the factors of what makes students of university of XYZ use KMSPico. By combining several models of User Acceptance of Information Technology (UTAUT), Protection Motivation Theory (PMT), and Security Belief Model. Sample collection of data by using a questionnaire and analyzed by Kendall Tau. The number of samples used in this study is 206 datas. Results of this study showed that University of XYZ students using KMSPico because KMSPico is effortless, performance, social influence, facilitating condition, perceived vulnerability, perceived severity of using KMSPico, self-efficacy, response efficacy, interest with KMSPico's information, and perceived benefits